PERFORMANCE EVALUATION AND FORMATION OF OPTIMAL PORTOFOLIO USING CAPM METHOD AND SINGLE INDEX MODEL IN PROPERTY AND REAL ESTATE SUB-SECTOR COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE 2015-2019 - Buluama, Andreas; Roy Sembel; Sidharta , Juaniva (Universitas Kristen Indonesia, 2021)
The purpose of this study is to determine the rate of return, risk of shares in the property sector, and the proportion of funds from the optimal portfolio formed. This study uses the Capital Asset Pricing Model and the Single Index Model. The sample used is 38 stocks of property and real estate companies listed on the Indonesia Stock Exchange. The results showed that there are 9 stocks that are included in the optimal portfolio based on the CAPM model with the proportion of BAPA funds 5.32%, DUTI 3.46%, EMDE 22.18%, FMII 6.01%, GMTD 38.37%, OMRE 10, 67%, PLIN 5.66%, RBMS 3.47% and RDTX 4.85%. The portfolio return is 2.19% per month and 26.34% per year with a risk of 5.44% or 18.84% per year. For the portfolio of the Single Index Model, there are 8 companies that enter the optimal portfolio with the proportion of DILD funds 6.60%, DUTI 7.05%, PUDP 2.51%, RODA 3.97%, OMRE 43.32%, FMII 5.86% , MTLA 22.61% and BKSL 8.08%. Portfolio return of 2.48% per month and 29.85% per year with a risk of 40.24% per year. Portfolios formed based on the CAPM method and the Single Index Model have a historical performance Sharpe ratio greater than the JCI. The CAPM portfolio is 0.326874 per month and 1.132326 per year, the single index model portfolio is 0.178304 per month and 0.6176624 per year, while the JCI is -0.107174 per month and -0.059494 per year. Keyword : CAPM, MVEP, Model Indeks Tunggal, Expected Return, Deviasi Standar.